2014
DOI: 10.1155/2014/850594
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Intervertebral Disc and Vertebra-Disc Junctions Zones as a Link in Etiopathogenesis of Idiopathic Scoliosis

Abstract: Background Context. There is no general accepted theory on the etiology of idiopathic scoliosis (IS). An important role of the vertebrae endplate physes (VEPh) and intervertebral discs (IVD) in spinal curve progression is acknowledged, but ultrastructural mechanisms are not well understood.Purpose. To analyze the current literature on ultrastructural characteristics of VEPh and IVD in the context of IS etiology.Study Design/Setting. A literature review.Results. There is strong evidence for multifactorial etiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 207 publications
(230 reference statements)
0
3
0
1
Order By: Relevance
“…In our study, MATN1 was the most abundantly expressed protein and has been found to form a complex with BGN/DCN, which in turn forms a link between aggrecan and collagen VI/II to form a stable extracellular matrix assembly [23]. MATN1 polymorphism and deficiency leading to altered cartilage architecture have been associated with increased incidence and severity of adolescent idiopathic scoliosis [24], and its abundant expression in our fetal disc emphasizes the need for its basal expression to maintain disc structure and homeostasis. It would be interesting to observe their expression in aging and degenerative disc tissues, and if found to be downregulated, it can be used for cell therapy.…”
Section: Discussionmentioning
confidence: 64%
“…In our study, MATN1 was the most abundantly expressed protein and has been found to form a complex with BGN/DCN, which in turn forms a link between aggrecan and collagen VI/II to form a stable extracellular matrix assembly [23]. MATN1 polymorphism and deficiency leading to altered cartilage architecture have been associated with increased incidence and severity of adolescent idiopathic scoliosis [24], and its abundant expression in our fetal disc emphasizes the need for its basal expression to maintain disc structure and homeostasis. It would be interesting to observe their expression in aging and degenerative disc tissues, and if found to be downregulated, it can be used for cell therapy.…”
Section: Discussionmentioning
confidence: 64%
“…These findings were confirmed three years later by [13]. Moreover, it was published that the histological abnormalities in the IVD in AIS are secondary to an altered mechanical environment [14][15][16][17][18]. These findings were based on the CTs of AIS patients, which showed that the IVDs contribute more to anterior spinal length compared to the contribution by the vertebrae, and suggested that the curve progression is not a primary vertebra growth disorder; rather, it is the result of altered mechanical loading.…”
Section: Introductionmentioning
confidence: 75%
“…Hal ini karena skoliosis cenderung mengalami kemajuan selama periode pertumbuhan masa pubertas. 15 Kemajuan deformitas tulang belakang yang mengalami skoliosis terjadi selama growth spurt remaja. 16 Ketidakseimbangan proses endokrin, khususnya selama pubertas, juga penting dalam skoliosis.…”
Section: Metode Penelitianunclassified